1993
DOI: 10.1007/bf02311373
|View full text |Cite
|
Sign up to set email alerts
|

Ambrosia elatior (L.) in Hungary (1989–1990)

Abstract: MAGDA JARAI-KOMLODI, MIKLOS JUHASZ SUMMARY. Weeds and among them

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 3 publications
0
13
0
2
Order By: Relevance
“…These are ragweed with mugwort leaves (= short ragweed; Ambrosia artemisiifolia = Ambrosia elatior), giant ragweed (Ambrosia trifida), perennial ragweed (Ambrosia psilostachya) and silver ragweed (Ambrosia tenuifolia). However, short ragweed is the most widely spread of all, not only in Western Europe but in Hungary too (Jµrai-Komlódi and Juhµsz 1993).…”
Section: Pollen Allergymentioning
confidence: 99%
“…These are ragweed with mugwort leaves (= short ragweed; Ambrosia artemisiifolia = Ambrosia elatior), giant ragweed (Ambrosia trifida), perennial ragweed (Ambrosia psilostachya) and silver ragweed (Ambrosia tenuifolia). However, short ragweed is the most widely spread of all, not only in Western Europe but in Hungary too (Jµrai-Komlódi and Juhµsz 1993).…”
Section: Pollen Allergymentioning
confidence: 99%
“…It has been also shown that there is a cross reactivity of Betula pollen with Corylus and Alnus pollen, as well as with apple, hazelnut and peach (Lazaro et al, 1999;Son et al, 1999) In previous years there have been few studies that deal with aeroallergen pollen in South Panonian valley (Ja´rai-Komlo´di and Juha´sz, 1993;Kadocsa et al, 1993;Juha´sz, 1997, 2002). However, there have been no studies of airborne Betula pollen, conducted in the State Union of Serbia and Montenegro.…”
Section: Introductionmentioning
confidence: 94%
“…The plain is bordered by the Carpathian Mountains, the Alps, the Dinaric Alps and the Balkan mountains. Recent phytogeographical studies that analysed the distribution and abundance of ragweed populations and aerobiological studies that examined the characteristics of airborne ragweed pollen have shown that countries with territory in the region of the Pannonian Plain, primarily Hungary (Jarai- Komlodi and Juhasz 1993;Járai-Komlódi 2000;Vitányi et al 2003;Juhász et al 2004;Apatini et al 2008), but also parts of Austria (Jäger 2000), Bosnia and Herzegovina (Janjić et al 2007), Croatia (Juhász et al 2004;Peternel et al 2005), Czech Republic (Rybnícek et al 2000), Romania (Juhász et al 2004), Serbia (Juhász et al 2004;Šikoparija et al 2006;Janjić et al 2007), Slovakia (Makovcová et al 1998;Bartková-Scevková 2003), Slovenia (Seliger 1998;Juhász et al 2004) and Ukraine (Mosyakin and Yavorska 2002), could be considered as severely infected by ragweed plants and threatened by ragweed airborne pollen.…”
Section: Introductionmentioning
confidence: 99%